The work environment factors that influence job satisfaction, and its impact on turnover intention: The case of executive level employees in the Malaysian Public Sector organizations - Abdul Rahim Zumrah; Kalsom Ali; Ahmad Najaa' Mokhtar; Muhammad Yusuf Khalid (Management and Business Academy, 2024)
Non-Indexed Publication